Aktywa niematerialne - problemy ewidencji utraty wartości w rachunkowości przedsiębiorstw w Republice Białorusi - Berezovskij, Vladimir; Gurko, Veronika (Non Material Assets - Problems Concerning Value Loss Evidence in Belarusian Republic Accountancy, 2005)
In practice, the non-material assets are known as an accountant course, which has impacted thelaw of Belarusian Republic.However, in state accountancy there are still unsolved problems in the area of such objectsvaluation. In our opinion, in further perspective by compilation of law topics, there should be takeninto account the experience of world accountancy practice, and the companies should be allowed tomake yearly tests in the field of assets value non-material losses, by using differentiate approachincluding its specific subject. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 151-154